ANTIOXIDANTS IN DIETARY SUPPLEMENTS: EFFECTS ON OXIDATIVE STRESS AND AGING (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article examines the role of antioxidants in dietary supplements, their impact on oxidative stress and aging processes. The mechanisms of action of antioxidants, their biochemical properties and potential for use in maintaining health and prolonging life are discussed.